Pengukuran Kinerja Sumber Daya Manusia dengan Pendekatan Human Resources Scorecard dan Alat Ukur OMAX (Objective Matrix) pada Bagian Produksi PT. Fajarindo Faliman Zipper - Sunny Phiong; Dadang Surjasa (JURNAL TEKNIK INDUSTRI, 2018)
PT. Fajarindo Faliman Zipper is a company that produces zipper. One of the problems faced by companiesrelated to the performance of human resources is less the achievement of company targets identification: targets ofproductivity each person that was still below the company's target. To evaluate the productivity of research, then thehuman resorce performance measurement needs to be done. Human resource performance measurement model is doneusing an approach HRSC and lays out the vision and mission into action measurable human resources contributions in 4perspectives: HPWS, HR System Aligment, HR Effisiency, HR Delivirable, and generate 18 KPI. While the measurementtool that is OMAX, after the results obtained in the evaluation done against the performance criteria isn’t reached withthe FTA. Then do a repair planning so that performance can be improved. Based on the results of the achievement asmeasured using the measuring instrument OMAX with traffic light system indicate that the level of productivity and timeof service are at level three and one so still requires intensive care. Based on the FTA approach then known to one of theoperators are less scrupulous. One of the proposals that can be given documents which already contain about problems,ways of prevention and improvement made corrective actions procedure and prevention.